Handbook of fluidization and fluid-particle systems - Yang, Wen-ching, 1939- (Chemical industries ;, 2003)
This reference details particle characterization, dynamics, manufacturing, handling, and processing for the employment of multiphase reactors, as well as procedures in reactor scale-up and design for applications in the chemical, mineral, petroleum, power, cement and pharmaceuticals industries. The authors discuss flow through fixed beds, elutriation and entrainment, gas distributor and plenum design in fluidized beds, effect of internal tubes and baffles, general approaches to reactor design, applications for gasifiers and combustors, dilute phase pneumatic conveying, and applications for.